2020
DOI: 10.1088/1755-1315/505/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Nutritional Performance of Black Soldier Fly (Hermetia illucens) Larvae Reared in Fermented Rice Straw and Duck Manure

Abstract: Black soldier fly larvae (BSFL) are known to convert organic wastes into useful biomass, of which the composition depends on the substrate. It is of interest whether feed protein can be sustainably obtained from waste materials by feeding them to BSFL. This study aimed to convert rice straw and duck manure into BSFL biomass for conversion of waste into animal feed. The growth parameters of BSFL fed with pure fermented rice straw, pure duck manure, and an equal parts mixture of the two as well as its nutritiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Other research conducted by Andari et al (34) reported similar range of protein content and fat content of food waste fed BSF, i.e., around 40% and 25% respectively. In addition, food waste fed BSF had significantly higher protein content and fat content than that of the manure fed BSF (35). The protein and fat content in food waste tended to be higher than manure.…”
Section: Resultsmentioning
confidence: 85%
“…Other research conducted by Andari et al (34) reported similar range of protein content and fat content of food waste fed BSF, i.e., around 40% and 25% respectively. In addition, food waste fed BSF had significantly higher protein content and fat content than that of the manure fed BSF (35). The protein and fat content in food waste tended to be higher than manure.…”
Section: Resultsmentioning
confidence: 85%
“…The BSFL can ingest various kinds of organic wastes, such as food waste, industrial by-products, abattoir waste, millet flakes, manure, and human faeces including sewage sludge ( Chia et al, 2020 ; Chia et al, 2018 ; Dobermann, Field & Michaelson, 2019 ; Ewusie et al, 2018 ; Lalander et al, 2019 ). Some difficult-to-degrade organic wastes, including rice straw, coconut endosperm, and palm waste, could be utilized by BSFL despite their high lignocellulose contents after pretreatment via biomass breakdown and fermentation ( Caruso et al, 2014 ; Dickinson et al, 2019 ; Manurung et al, 2016 ; Mohd-Noor et al, 2017 ; Pamintuan, Agustin & Deocareza, 2020 ). Likewise, the degradation of high fiber substrates, such as palm kernel meal is recommended prior to use as a BSFL feed ( Caruso et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to find the perfect pure food substrate for BSF rearing. Instead, co-digest wastes have given a better growth of BSFL, especially for difficult-to-degrade organic wastes ( Pamintuan, Agustin & Deocareza, 2020 ; Sideris et al, 2021 ). As a consequence, the combination of various organic wastes has been evaluated as potential high-quality and low-cost BSFL diets ( Gold et al, 2020 ; Jucker et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Black soldier fly (BSF) larvae, an important environmental insect, are saprophytic and have a wide range of food sources. BSF larvae can quickly convert organic waste (such as food waste [ 16 , 17 ], poultry manure [ 18 , 19 , 20 ], straw [ 21 , 22 ], sewage sludge [ 23 ], and organic leachates [ 24 , 25 ]) into stable biological fertilizers and their biomass. Additionally, BSF larvae were found to produce broad-spectrum antimicrobial peptides with different antibacterial activities according to the diet [ 26 ], which can reduce a variety of pathogens [ 27 ].…”
Section: Introductionmentioning
confidence: 99%